The Exposure of the Roma and the Remaining Istrian Population to Victimization by Criminal Acts - Mirjana Radetić-Paić (Migracijske i etničke teme, 2010)
The aim of this study was to determine whether the Roma (N = 200) as a minority group in Istria were more exposed to criminal acts (more victimised) than the remaining Istrian population (N = 200) in the observed period. It was assumed that the Roma were more exposed to criminal acts than the remaining Istrian population because of the fact that they were members of a minority group with a specific lifestyle and culture in Istria, who are significantly exposed to prejudices, resistance, marginalization and isolation. In data processing, the χ2 test and the discriminatory analysis were used, along with the calculation of marginal frequencies on all observed variables. The contribution of this paper is that it illuminates the larger problem of the Roma as a specific minority group’s exposure to certain criminal acts compared to the rest of the population. It is therefore necessary to devote more attention to Roma issues, and to encourage those in power systematically to solve the same at the international, national and local level in particular, and also to find the mechanisms for protection of human rights and suppression of discrimination and segregation of any kind.